Status of oil palm tissue culture in Malaysia: a review / Mohamad Amirul Farid Abdullah - Abdullah, Mohamad Amirul Farid (Faculty of Plantation and Agrotechnology, 2017)
The Malaysian national average oil yield had been stagnating at 3.5 to 3.9 t/ha/year over the past two decades. Because of the expanding worldwide requests for vegetable oils coupled with difficulties in production endeavors, there is an important need to enhance the productivity. Current oil palm (Elaeis guineensis) planting materials are delivered through the hybridization of dura x pisifera (DxP). Tissue culture is one of the alternatives in order to quicken and catch the maximum yield of oil palm. Oil palm tissues culture in Malaysia has been successful but was still faced with problems such as ortet selection and availability, floral abnormality and low embryogenesis rate. Significant effort on recloning may mitigate this problems. The production of clonal oil palm is still low which is 1.9 million ramets in 2005 and increase to 2.53 million ramets in 2009. There is comprehensive efforts such as set up ortet garden, develop The Malaysian Standard on Oil Palm Ortet Selection for Cloning – Specification and others to set selection standard and permitting approaches to ensure bona fide producers.